Determination of Source Parameters of Simple-shaped Geologic Subsurface Structures from Self-potential Anomalies Using Enhanced Local Wavenumber Method - Luan, Pham Thanh Luan; Duc Minh, Vu; Oksum, Erdinc (VNU Journal of Science: Mathematics - Physics, 2019)
Abstract: Simple geometry model structures can be useful in quantitative evaluation of self-potential data. In this paper, we solve local wavenumber equation to estimate the horizontal position, the depth and the type of the causative source geometry by using a linear least-squares approximation. The advantages of the algorithm in determining the horizontal position and depth measure are its independence to shape factor of the sources and also its simple computations. The algorithm is built in Matlab environment. The validity of the algorithm is illustrated on variable noise-free and random noise included synthetic data from two-dimensional (2-D) models where the achieved parametric quantities coincide well with the actual ones. The algorithm is also utilized to real self-potential data from Ergani Copper district, Turkey. The results from the actual data application are in good agreement with the published literature for the study area. The source code of the algorithm is available from the authors on request. Keywords : Local wavenumber, Self-potential, a linear least-squares approximation, Ergani copper field.